PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI PADA DEALER PT. HASJRAT TOYOTA DI KOTA TERNATE - Zulfikri Andili (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of brand equity on the Toyota car purchase decision process, also to determine the effect of consumer satisfaction on the Toyota car purchase decision process and to find out that the consumer satisfaction variable as a moderating variable can strengthen or weaken the brand equity relationship to Toyota car consumer purchasing decisions in Ternate City. . Using the SmartPls type of research with 90 respondents, the results of the research on brand equity variables have a positive and significant effect on purchasing decisions. The variable of consumer satisfaction has a positive and significant effect on purchasing decisions and consumer satisfaction can moderate brand equity on purchasing decisions, which means that customer satisfaction significantly moderates the influence of brand equity on purchasing decisions. in Ternate City.